Hydrogeochemical Assessment of Groundwater of Taluka Chachro, Thar Parker, district, Sindh, Pakistan - Samtio, Muhammad Soomar; Hakro, Asghar A. A. D.; Rajper, Khadim Hussain; Mastoi, Abdul Shakoor; Rajper, Riaz Hussain; Lashari, Rafique Ahmed (International Journal of Economic and Environmental Geology, 2023)
The study was conducted to evaluate the hydrogeochemistry of groundwater. Twenty-six groundwater samples were analysed for the groundwater quality of Chachro Taluka. The EC and TDS contents in most of the water samples were above WHO (2011) recommended limits. Almost all water samples collected from dugwells located in the study area have elevated concentrations of Na and Cl exceeding the WHO guidelines. Results of Ca, and Mg show that 92% and 96% of groundwater samples were within the prescribed limit respectively. Whereas, HCO3, SO4, and NO3 contnets of 88%, 77%, and 69% respectively are also above the guidelines. Statistical results revealed a dominating trend among the cations of Na+>Ca+2>Mg+2>K+ and anions occur in the order of abundance, as Cl->HCO3->SO4 ->NO3, respectively. The water quality index (WQI) shows that 15% groundwater samples belong to poor category, and 35% water samples were found belonging to very poor category.While, remaining 50% wells were found unsuitable for drinking purpose